Compliance with the 24-Hour Movement Behavior Guidelines and Associations with Adiposity in European Preschoolers: Results from the ToyBox-Study - Decraene, Marga (Int J Environ Res Public Health, 2021)
In 2019, the World Health Organization (WHO) published 24 h movement behavior guidelines for preschoolers with recommendations for physical activity (PA), screen time (ST), and sleep. The present study investigated the proportion of preschoolers complying with these guidelines (on a total week, weekdays and weekend days), and the associations with adiposity. This cross-sectional study included 2468 preschoolers (mean age: 4.75 years; 41.9% boys) from six European countries. The associations were investigated in the total sample and in girls and boys separately. PA was objectively assessed by step counts/day. Parent-reported questionnaires provided ST and sleep duration data. Generalized estimating equations were used to analyze the association between guideline compliance and adiposity indicators, i.e., body mass index (BMI) z-score and waist to height ratio (WHR). Only 10.1% of the preschoolers complied with the 24 h movement behavior guidelines, 69.2% with the sleep duration guideline, 39.8% with the ST guideline and 32.7% with the PA guideline. No association was found between guideline compliance with all three movement behaviors and adiposity. However, associations were found for isolated weekday screen time (BMI z-scores and WHR: p = 0.04) and weekend day sleep duration (BMI z-scores and WHR: p = 0.03) guideline compliance with both lower adiposity indicators. The latter association for sleep duration was also found in girls separately (BMI z-scores: p = 0.02; WHR: p = 0.03), but not in boys. Longitudinal studies, including intervention studies, are needed to increase preschoolers’ guideline compliance and to gain more insight into the manifestation of adiposity in children and its association with 24 h movement behaviors from a young age onwards.